Developmental genoarchitectonics as a key tool to interpret the mature anatomy of the chondrichthyan hypothalamus according to the prosomeric model - Santos-Durán, Gabriel N.; Ferreiro-Galve, Susana; Mazan, Sylvie; Anadón, Ramón; Rodríguez-Moldes, Isabel; Candal, Eva (Frontiers in Neuroanatomy, 2022)
The hypothalamus is a key vertebrate brain region involved in survival and physiological functions. Understanding hypothalamic organization and evolution is important to decipher many aspects of vertebrate biology. Recent comparative studies based on gene expression patterns have proposed the existence of hypothalamic histogenetic domains (paraventricular, TPa/PPa; subparaventricular, TSPa/PSPa; tuberal, Tu/RTu; perimamillary, PM/PRM; mamillary, MM/RM), revealing conserved evolutionary trends. To shed light about the functional relevance of these histogenetic domains, the present work aims to interpret the location of developed cell groups according to the prosomeric model in the hypothalamus of the catshark Scyliorhinus canicula, a representative of Chondrichthyans (the sister group of Osteichthyes, at the base of the gnathostome lineage). To this end, we review in detail the expression patterns of ScOtp, ScDlx2 and ScPitx2 as well as Pax6-immunoreactivity in embryos at stage 32, when the morphology of the adult catshark hypothalamus is already organized. We also propose homologies with mammals when possible. The present study provides a comprehensive tool to better understand previous and novel data on hypothalamic development and evolution.